Personal, work and contextual factors that influence nurse in the presence of an adverse event - Vargas Bermúdez, Zeidy (2016)
Introduction. An adverse event is defined as an unexpected situation that damages the patient and is a product of the interaction with the health team and the institution. The aim of this study is to describe the opinion of nurses about the personal, labor and contextual factors that influence the presence of an adverse event in the area of medicines Rafael Angel Calderon Guardia Hospital.Method. The participant population consisted of 38 professionals working in the field of medicine. Exclusion criteria are adverse events infections and pressure ulcers. The variables studied are socio-demographic characteristics of the population, knowledge of the concept of adverse event report itself and the opinion of the condition of infrastructure, equipment, location of users and the distribution of them as a factor related to the occurrence of adverse events. The study is descriptive traversal with a validated self-administered questionnaire.Result. Most of the population is aware of the conceptualization of an adverse event, believe that there is no relationship between the condition of the infrastructure and equipment with the appearance of events. They say that the location of patients and number assigned by professional influences the occurrence of adverse events.Conclusion. The conceptual definition of adverse event is known not show a reckless behavior before the report. The ratio of patients per professional, quality and location thereof are directly related to adverse events in this institution.